Total Airway Count on Computed Tomography and the Risk of Chronic Obstructive Pulmonary Disease Progression. Findings from a Population-based Study - Miranda Kirby; Naoya Tanabe; Wan C. Tan; Guohai Zhou; Ma’en Obeidat; Cameron Hague; Jonathon Leipsic; Jean Bourbeau; Don D. Sin; James C. Hogg; Harvey O. Coxson; Jean Bourbeau; et al. (2017)
Rationale: Studies of excised lungs show that significant airway attrition in the “quiet” zone occurs early in chronic obstructive pulmonary disease (COPD).Objectives: To determine if the total number of airways quantified in vivo using computed tomography (CT) reflects early airway-related disease changes and is associated with lung function decline independent of emphysema in COPD.Methods: Participants in the multicenter, population-based, longitudinal CanCOLD (Canadian Chronic Obstructive Lung Disease) study underwent inspiratory/expiratory CT at visit 1; spirometry was performed at four visits over 6 years. Emphysema was quantified as the CT inspiratory low-attenuation areas below −950 Hounsfield units. CT total airway count (TAC) was measured as well as airway inner diameter and wall area using anatomically equivalent airways.Measurements and Main Results: Participants included never-smokers (n = 286), smokers with normal spirometry at risk for COPD (n = 298), Global Initiative for Chronic Obstructive Lung Disease (GOLD) I COPD (n = 361), and GOLD II COPD (n = 239). TAC was significantly reduced by 19% in both GOLD I and GOLD II compared with never-smokers (P < 0.0001) and by 17% in both GOLD I and GOLD II compared with at-risk participants (P < 0.0001) after adjusting for low-attenuation areas below −950 Hounsfield units. Further analysis revealed parent airways with missing daughter branches had reduced inner diameters (P < 0.0001) and thinner walls (P < 0.0001) compared with those without missing daughter branches. Among all CT measures, TAC had the greatest influence on FEV1 (P < 0.0001), FEV1/FVC (P < 0.0001), and bronchodilator responsiveness (P < 0.0001). TAC was independently associated with lung function decline (FEV1, P = 0.02; FEV1/FVC, P = 0.01).Conclusions: TAC may reflect the airway-related disease changes that accumulate in the “quiet” zone in early/mild COPD, indicating that TAC acquired with commercially available software across various CT platforms may be a biomarker to predict accelerated COPD progression.